Historic Wooden Architecture in Europe and Russia : Evidence, Study and Restoration - Khodakovsky, Evgeny; Skjold Lexau, Siri (Birkhäuser, 2015)
This reference book explains the current state of research on contemporary methods and procedures for dealing with historic timber structures. It summarizes the results of a buildings researchers' conference in late 2014 in Prague, which was dedicated to the three main aspects essential to dealing with historic timber structures: construction, architecture history, and repair and maintenance.